2021
DOI: 10.1016/j.jmig.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Outcome after CO2 Laser Vaporization versus Cystectomy in Women with Ovarian Endometrioma: A Comparative Study

Abstract: To assess the postoperative likelihood of conception in patients with endometriomas managed by either CO 2 laser vaporization or cystectomy. Design: A retrospective study with prospective recording of data. Setting: University hospital. Patients: One hundred and forty-two patients with symptomatic endometriomas. Interventions: Patients underwent a standardized laparoscopic stripping technique (Group 1) or cyst vaporization with CO 2 fiber laser (Group 2). Patients wishing to become pregnant were allowed to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…[3][4][5] Data about endometrioma ablation using energies with limited depth thermal spread such as CO 2 laser and plasma energy reported good results in terms of postoperative pregnancy rates and recurrence risk. [6][7][8][9][10][11] We also previously reported comparable pregnancy rates in a case series of women managed by either ablation using plasma energy or cystectomy, but with significant differences in endometriosis severity. 12 Although it has been demonstrated that endometrioma drainage is associated with short-term recurrences, the goal to protect the ovarian reserve justifies the choice of drainage.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…[3][4][5] Data about endometrioma ablation using energies with limited depth thermal spread such as CO 2 laser and plasma energy reported good results in terms of postoperative pregnancy rates and recurrence risk. [6][7][8][9][10][11] We also previously reported comparable pregnancy rates in a case series of women managed by either ablation using plasma energy or cystectomy, but with significant differences in endometriosis severity. 12 Although it has been demonstrated that endometrioma drainage is associated with short-term recurrences, the goal to protect the ovarian reserve justifies the choice of drainage.…”
mentioning
confidence: 52%
“…19,21 Pregnancy rates in studies comparing women managed by either cystectomy or ablation using CO 2 laser varied from, respectively, 38.1% and 44.4% at 5 years after the surgery 22 to, respectively, 72.2% and 74.3% after a mean follow up averaging 3 years. 10 Case series including women undergoing ovarian ablation by plasma energy and getting pregnant in up to 73% of cases were reported by our team, and this study population may partially overlap with the one included in this study. 23,24 We should emphasize that a majority of women managed by ablation and simple drainage underwent surgical procedures for deep endometriosis involving the digestive tract.…”
Section: Discussionmentioning
confidence: 94%
“…Pre-procedure aspiration of the endometrioma is not part of the local policies of the participating centers and will not be performed. Surgery will be achieved according to local standards [ 5 , 6 , 19 ]. No efforts were done to standardize the surgical modalities.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery aims at increasing the chances of natural conception and has the beneficial effect of relieving symptoms [ 6 , 7 ]. Among uncontrolled studies, the overall mean pregnancy rate is nearly 50% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our daily practice, we have introduced ablation using CO2 fiber laser technology: it is simple, easy to use, and has the advantage of eliminating the “surgeon's experience” factor ( 13 ). We have already been able to report encouraging results in terms of ovarian reserve preservation, postoperative pregnancy rates, recurrence risk and ovarian responsiveness in ART ( 14 16 ).…”
Section: Minimally Invasive Surgery For Endometriosis-associated Infe...mentioning
confidence: 96%